2020
DOI: 10.1002/zaac.202000103
|View full text |Cite
|
Sign up to set email alerts
|

Group 13 Metal Halide Based Coordination Polymers of Al, Ga, In and 2,4,6‐Tri(4‐pyridyl)‐1,3,5‐triazine

Abstract: Four isotypic one-dimensional coordination polymers (CP) were synthesized using the group 13 metal halides AlBr 3 , GaCl 3 , GaBr 3 , and InI 3 and the tridentate ligand 2,4,6-tri(4-pyridyl)-1,3,5-triazine (tpt) serving as bidentate linker. The neutral one-dimensional CPs 1 ϱ [AlBr 3 (tpt)], 1 ϱ [GaCl 3 (tpt)], 1 ϱ [GaBr 3 (tpt)], and 1 ϱ [InI 3 (tpt)] are constituted by zigzag-shaped chains in the crystal structure, in which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, the ν(C=N) ring vibration modes for the uncoordinated N-donor ligands (bipy: ν(C=N) = 1587 cm À 1 ; bpe: ν(C=N) = 1594 cm À 1 ; bpa: ν(C=N) = 1593 cm À 1 ) were not observed. [29] The experimental powder diffractogram of 3 indicates the successful formation of CP 3. Additional reflections, which could be assigned to InCl 3 and at least one unknown, further crystalline phase are observed.…”
Section: Synthesis Ir Spectroscopy and Thermal Analysismentioning
confidence: 95%
See 3 more Smart Citations
“…Furthermore, the ν(C=N) ring vibration modes for the uncoordinated N-donor ligands (bipy: ν(C=N) = 1587 cm À 1 ; bpe: ν(C=N) = 1594 cm À 1 ; bpa: ν(C=N) = 1593 cm À 1 ) were not observed. [29] The experimental powder diffractogram of 3 indicates the successful formation of CP 3. Additional reflections, which could be assigned to InCl 3 and at least one unknown, further crystalline phase are observed.…”
Section: Synthesis Ir Spectroscopy and Thermal Analysismentioning
confidence: 95%
“…The longer InÀ I distances found for CP 4 can be explained by the increase in coordination number from five to six. [29] Altogether, the chlorine containing coordination polymers…”
Section: Crystal Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of studies have demonstrated the coordination nanostructures by altering organic ligands, such as carboxylate, 3,5,12,18 hydroxyl, 14,20,21 pyridine, 9,22-25 and triazine. [26][27][28][29][30] The triazine derivatives are important in a range of areas as ligands for supramolecular self-assembly of more complex mixed layers, hence it may be interesting to study the coordination properties of the triazine derivatives. In this article, we fabricated different coordination nanostructures by 4,4 0 ,4 00 -(1,3,5-triazine-2,4,6-triyl) tribenzoic acid (TATB) molecules coordinating with Cu 2+ or Fe 3+ ion with different concentrations on highly oriented pyrolytic graphite (HOPG) surface.…”
Section: Introductionmentioning
confidence: 99%